Training and Assistance for Clean Living Patterns by Utilizing School Facilities at SMA Negeri 1 Liwa - Erawati, Reni; Rahmanda, Rani; Laksono , Riri Zaniah; Yulisatria, Guntur (Jurnal Abdimas Nusantara, 2024)
Clean living patterns are an important aspect in creating a healthy and comfortable school environment. SMA Negeri 1 Liwa plays an active role in forming a clean and healthy young generation. This clean living pattern training and mentoring is intended to increase awareness of clean living behavior through the use of school facilities among SMA Negeri 1 Liwa students by collaborating between SMA Negeri 1 Liwa teachers and Muhammadiyah Kotabumi University Teaching Assistance students. Students act as facilitators and mentors in school cleanliness activities, such as waste management, optimization of school facilities, and education about the importance of clean living patterns guided by SMA Negeri 1 Liwa teachers starting from the data collection stage until the implementation process is complete, using qualitative descriptive methods. Optimal utilization of school facilities such as trash cans, sinks, and school cleanliness areas can increase students' awareness of the importance of maintaining environmental cleanliness. In addition, the ongoing cleanliness education program also has a positive impact on students' behavior in implementing clean living patterns. The findings show that student involvement in utilizing school facilities makes a significant contribution to the creation of a healthy school environment and supports the teaching and learning process.